Regulation of Inflammation Pathways and Inflammasome by Sex Steroid Hormones in Endometriosis - García-Gómez, Elizabeth; Vázquez-Martínez, Edgar Ricardo; Reyes-Mayoral, Christian; Cruz-Orozco, Oliver Paul; Camacho-Arroyo, Ignacio; Cerbón, Marco (Frontiers in Endocrinology, 2020)
Endometriosis is a gynecological disorder characterized by the growth of endometrial tissue (glands and stroma) outside the uterus, mainly in the peritoneal cavity, ovaries, and intestines. This condition shows estrogen dependency and progesterone resistance, and it has been associated with chronic inflammation, severe pain, and infertility, which negatively affect the quality of life in reproductive-age women. The molecular mechanisms involved in the pathogenesis of endometriosis are not completely understood, however, inflammation plays a key role in the pathophysiology of the disease, mainly by altering the function of immune cells (macrophages, T cells, natural killer cells ) and increasing the levels of pro-inflammatory mediators in the peritoneal cavity, endometrium, and blood. These immune alterations, inhibit apoptotic pathways and promote adhesion and proliferation of endometriotic cells, as well as angiogenesis and neurogenesis in endometriotic lesions. It has been demonstrated that hormonal alterations in endometriosis are related to the inflammatory unbalance in this disease. Particularly, steroid hormones (mainly estradiol) promote the expression and release of pro-inflammatory factors. In turn, excessive inflammation observed in endometriosis contributes to progesterone resistance and high estrogen sensitivity by modulating sex steroid receptors expression and increasing aromatase activity. In addition, dysregulation of the inflammasome pathway, mediated by an alteration of cellular responses to steroid hormones, participates in disease progression through preventing cell death, promoting adhesion, invasion, and cell proliferation in lesions. Furthermore, inflammation is involved in endometriosis-associated infertility, due to a pro-inflammatory response mounted in the endometrium, which alters their receptivity by impairing biochemical responses and decidualization. The purpose of this review is to present an overview of current research about the role of inflammation and the inflammasome in the pathogenesis of endometriosis as well as to clarify the probable molecular role of sex hormones in the alteration of immune and inflammatory responses in this disease.